Pengaruh Environmental Concerns, Attitude, Dan Product Performance Terhadap Minat Beli Pakaian Ramah Lingkungan Pada Generasi Z - Surun, Miftahu; Harsoyo, Titik Desi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study was conducted to examine the effect of Environmental Concerns, Attitude, and Product Performance on buying interest in environmentally friendly clothing in generation Z. The research method used is quantitative research method and survey through questionnaires distributed to 100 respondents who are generation Z who have knowledge about environmentally friendly clothing. The results showed that Environmental Concerns, Attitude, and Product Performance have a significant positive effect on buying interest in environmentally friendly clothing in generation Z. Industries that produce environmentally friendly clothing must provide clothing care education through socialization or short advertisements and how to manage clothing waste to the public.